“ Meningkatkan Minat Belajar Anak di Panti Asuhan Kasih Setia Melalui Mini Project Ilmu Kesejateraan Sosial” - Meidona Hutapea Mey; Berlianti (Pengelola Jurnal Politeknik Negeri Ketapang, 2022)
We cannot deny that the pandemic period makes children bored and bored due to the school system from home or online, it is not uncommon for children to feel lazy which causes their interest in learning to decrease, not to mention the children who are at the Kasih Setia Orphanage. The caretakers of the orphanage must think of ways to increase the children's interest in learning in the orphanage. Through PKL activities from the Social Welfare Study Program, Faculty of Social and Political Sciences, it is hoped that it will have a positive impact on children at the Kasih Setia Orphanage.